A novel CRIg‐targeted complement inhibitor protects cells from complement damage. Issue 11 (11th August 2014) - Qiao, Qian; Teng, Xiaoyan; Wang, Na; Lu, Renquan; Guo, Lin; Zhang, Xin; Du, Yiqun; Wang, Wenjuan; Chen, Suning; Wu, Qian; He, Guangsheng; Wang, Yingwei; et al.
Abstract : The inappropriate activation of complement may contribute to various immune diseases. The alternative pathway (AP) predominates during complement activation regardless of the initiating pathways. Hence, the main AP regulator factor H (FH) holds great potential as an attractive therapeutic intervention. In addition, complement receptor of the immunoglobulin superfamily (CRIg) has been demonstrated to inhibit AP and, more notably, still specifically binds to C3b/iC3b. We thus developed novel CRIg‐targeted complement inhibitors by connecting the functional domains of CRIg and FH, which we termed CRIg‐FH and CRIg‐L‐FH. CRIg‐L‐FH, slightly more potent than CRIg‐FH, considerably inhibited both AP‐ and also classical pathway (CP)‐mediated hemolysis and successfully eliminated the deposition of C3b/iC3b. Kinetic analysis further revealed that the binding affinity constant ( K D ) of CRIg/FH was in the micromolar range, consistent with its long‐lasting binding to complement‐attacked cells. CRIg‐L‐FH efficiently protected aberrant erythrocytes of patients with paroxysmal nocturnal hemoglobinuria (PNH) from AP‐and CP‐mediated complement damage (IC50 was 22.43 and 64.69 nM, respectively). Moreover, CRIg‐L‐FH was found to inhibit complement activation induced by the anti‐Thy1 antibody in a mesangiopro‐liferative glomerulonephritis (MPGN) rat model. Hence, CRIg‐L‐FH protects glomerular mesangial cells (GMCs) from complement‐mediated injury and proliferative lesions. These findings strongly suggest that CRIg/FH is a potential therapeutic drug candidate for a range of complement‐mediated diseases.—Qiao, Q., Teng, X., Wang, N., Lu, R., Guo, L., Zhang, X., Du, Y., Wang, W., Chen, S., Wu, Q., He, G., Wang, Y., and Hu, W., A novel CRIg‐targeted complement inhibitor protects cells from complement damage. FASEB J. 28, 4986–4999 (2014). www.fasebj.org